2021
DOI: 10.1002/1873-3468.14188
|View full text |Cite
|
Sign up to set email alerts
|

Pseudouridines in RNAs: switching atoms means shifting paradigms

Abstract: Ting-Yu Lin and Rahul Mehta contributed equally to this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 100 publications
(153 reference statements)
0
14
0
Order By: Relevance
“…Better thermal stability. Ψ-A, Ψ-G, Ψ-U, and Ψ-C pairs are formed at several sites in structured RNAs that are conserved across species to stabilize important RNA duplexes and improve RNA-protein interactions (Lin et al, 2021).…”
Section: Pseudouridylationmentioning
confidence: 99%
“…Better thermal stability. Ψ-A, Ψ-G, Ψ-U, and Ψ-C pairs are formed at several sites in structured RNAs that are conserved across species to stabilize important RNA duplexes and improve RNA-protein interactions (Lin et al, 2021).…”
Section: Pseudouridylationmentioning
confidence: 99%
“…The key modification turned out to be the replacement of uridine residues with pseudouridine (Psi), the most common RNA modification, for example occurring in nonimmunogenic RNAs, such as transfer RNAs or ribosomal RNAs [56]. At the molecular level, Lin and colleagues showed that Psi residues establish additional bonds with neighbouring atoms and thereby strengthen RNA–RNA and RNA–protein interactions [57]. In case of messenger RNA, the presence of Psi sites enhances the lifetime and the translation efficiency of the mRNA and reduces unwanted innate immune reactions, such as inflammation.…”
Section: Covid Vaccines and Mrnamentioning
confidence: 99%
“…The detection of Ψ is based on the selective labeling by N3‐[ N ‐cyclohexyl‐ N ′‐β‐(4‐methylmorpholinium)ethylcarbodiimide (CMC), which can be identified by reverse transcription or next‐generation sequencing (NGS) techniques (T. Y. Lin et al, 2021 ). Recently it was shown, that nanopore sequencing might offer the possibility of a label‐free method to detect and quantify the incorporation of Ψ in different types of RNAs (Begik et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%